PROBLEMS AND SOLUTIONS OF THE SILT SLUDGE UTILIZATION ISSUES AT WASTE TREATMENT FACILITIES OF NUR-SULTAN CITY - Yermekov M.T.; Rozhkova O.V.; Tolysbayev Ye.T.; Zhakipbekov Zh.N.; Merkureva S.N.; Schefer V.I.; Ivanovich V.V. (Academic Scientific Journal of Chemistry, 2020)
Effective management of wastewater sludge is currently one of the most pressing environmental problems in Nur-Sultan city, which becomes more acute year by year and requires immediate solution. Wastewater sludge is almost completely stored at the treatment facilities, which turns them into a source area of bacteriological and toxicological hazard. For this reason, the most urgent problem now is the development of new sustainable and zero waste technologies that can effectively expedite the reduction of silt sludge and lead to a significant decrease in their final volume. This article analyzes various methods of sludge disposal. It is shown that of all possible technology options with admissible environmental impact and the best economic indicators, the most acceptable is the method of thermo-catalytic oxidation of wastewater sludge in a semi fluidized bed of the catalyst, the use of which can fundamentally change the situation with the sludge disposal. Also, the article studied the composition and carried out measurements of silt sludge contamination with heavy metals and oil products at wastewater treatment plants of Nur-Sultan city. It is pointed out that the LOC for the TPH-in-soil is 1.5 g/kg, from which it can be concluded that there is a significant excess in the wastewater sludge for this indicator, and studies for the heavy metals presence in the wastewater sludge showed that sediments can have a toxic effect and are classified as 4 class of hazard.